The increase of fibroblast cells number in rat (rattus norvegicus) gingival wound after the application of moringa (moringa oleifera lam) fruit oil - Bahruddin Thalib; Nurhayaty Natsir; Alqarama M. Thalib; Rafikah Hasyim; Asmawati (DiscoverSys Inc., 2020)
Objective: To determine the increase of fibroblast cell number in the rat (Rattus norvegicus) gingival wound after the application of moringa (Moringa oleifera Lam) fruit oil.Material and Methods: This study was an experimental post-test control group design using 18 male Wistar rats (Rattus norvegicus) that was divided into three groups. The sample was previously incised with a length of 4 mm using scalpel 15. Group 1 was applied with moringa fruit oil, group 2 was given aspirin, and group 3 was given at 0.5% CMC. The application was carried out every 24 hours, then on the third and seventh day, the rats were euthanized for histological preparations and then observed under the electric microscope. The length of the lesion was measured on the first, third, and seventh days. The fibroblast was then observed by counting the number of fibroblast cells per field of view using an Olympus C-21 microscope with an Optilab Advances camera with a 40x, 100x magnification, and 400x. The data were processed and analyzed using the SPSS Version 21 program. This study used a t-test to see the differences between the treatment group and the control group, and the Least Significantly Difference (LSD) test was used to see the size of the difference.Results: This study showed a significant increase in the number of fibroblasts in rat gingival mucosa on the third and seventh daysConclusion: Moringa (Moringa oleifera Lam) fruit oil affects increasing the number of fibroblasts on the rat gingival mucosa (Rattus norvegicus).